(untitled) (Global Journal of Management and Business Research, 2013)
This research work-the introduction of GSM services in Anyigba community and its impact on students expenditure pattern is aimed at examining the pre and post GSM introduction expenditure pattern of students with a view to finding out whether the introduction of GSM has any significant impact on students expenditure pattern or not. Data were collected using the primary and secondary sources. Questionnaire and personal interview were the primary method used while journal material/article formed the bulk of the secondary material used. Chi-square was used to analyse the data collected. It was found out from the analysis that a significant relationship exist between the introduction of GSM service in Anyigba and students expenditure pattern in the sense that after the introduction of GSM, the amount spent on it takes priority over budgeted amount on academic activities, food, transport etc. It is therefore recommended that students should maintain a balance in their expenditure. In other words, they should scale down on the amount spent on GSM and reorder their priorities in the interest of their major purpose for coming to Anyigba-academic pursuit.